2017
DOI: 10.1002/14651858.cd007026.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrolysin for acute ischaemic stroke

Abstract: The findings of this Cochrane Review do not demonstrate clinical benefits of cerebrolysin for treating acute ischaemic stroke. We found moderate-quality evidence of an increase in non-fatal SAEs with cerebrolysin use but not in total SAEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…To date five meta-analyses of RCTs investigating the efficacy of Cerebrolysin in acute ischemic stroke have been performed [ 38 42 ]. Three, evaluating aggregate data from up to seven trials involving 1501 to 1779 patients, concluded that the medication did not demonstrate any clinical benefit [ 38 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date five meta-analyses of RCTs investigating the efficacy of Cerebrolysin in acute ischemic stroke have been performed [ 38 42 ]. Three, evaluating aggregate data from up to seven trials involving 1501 to 1779 patients, concluded that the medication did not demonstrate any clinical benefit [ 38 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date five meta-analyses of RCTs investigating the efficacy of Cerebrolysin in acute ischemic stroke have been performed [ 38 42 ]. Three, evaluating aggregate data from up to seven trials involving 1501 to 1779 patients, concluded that the medication did not demonstrate any clinical benefit [ 38 , 41 , 42 ]. In particular, a Cochrane Review did not find Cerebrolysin to be useful, but several trials were excluded from the analysis since treatment initiation exceeded the review protocol’s prespecified 48-h stroke-onset window [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 One recent Cochrane review based on 6 trials evaluates the effects of cerebrolysin in acute ischemic stroke and concludes that the use of cerebrolysin has no effect on fatality. 9,10 Five of the included trials were small, and in the largest trial, the comparison groups were not balanced for prognostic factors. The loss to follow-up was considerable in the trials.…”
Section: See Related Article P E245mentioning
confidence: 99%
“…Despite the lack of evidence from systematic reviews for efficacy regarding both fatality 9 and functional outcome, 14 cerebrolysin has been used in several countries, with limited healthcare resources in Asia and Eastern Europe. Although subgroup-and post hoc analyses suggested potential benefit of cerebrolysin, these claims should be currently considered only hypotheses.…”
Section: See Related Article P E245mentioning
confidence: 99%